Controladores ressonante e repetitivo modificados para o tratamento de sinais com período variante no tempo - Castro, Rafael da Silveira (2015)
This dissertation proposes novel control schemes in order to track periodic references and/or reject periodic disturbances with time-varying frequency. The proposed methodology is based on a 𝜃-domain concept, where the interest signals possess a constant period. By employing the Internal Model Principle, this domain allows the design of linear controllers that ensure tracking and/or rejection performance to the targeted class of signals. The main objective is, then, to transform these controllers dynamical description from 𝜃-domain to the usual time domain. This idea was explored to modify the Resonant and Repetitive Controllers, traditional approaches based on the Internal Model Principle, yielding Transformed Resonant and Repetitive Controllers, the proposed control schemes that deal with large period variations. Robust control methodologies based on Linear Matrix Inequalities are presented in order to synthesize the controllers parameters and assure robust closed-loop stability and performance. The advantages of the proposed control architectures, in comparison to traditional strategies, are evaluated by simulated applications with time-varying period signals, such as eccentric direct current motors, frequency inverters and wind turbines. Besides the continuous time formulation, this work presents discrete time synthesis methodologies and implementation of the Transformed Resonant and Repetitive Controllers. In the end, experimental results with an eccentric direct current motor show the benefits of the proposed controllers in contrast to the traditional ones.